Overview of gadget use by 8th grade students - Septia Rachman Prasasti; Ita Apriliyani; Arni Nur Rahmawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The rapid development of digital technology has increased gadget use among adolescents, particularly junior high school (SMP) students. While gadget use can be beneficial as a learning medium and source of information, it also has the potential to negatively impact physical, emotional, and social health if not used wisely. Purpose: This study aims to examine gadget use among eighth-grade students. Method: The study employed a quantitative descriptive design with a survey method and a cross-sectional approach. The sample was determined using the Slovin formula and drawn using a non-probability purposive sampling technique, resulting in 60 respondents from a total population of 150 eighth-grade students. Data collection was conducted using a questionnaire structured based on gadget use indicators. Univariate analysis was conducted using frequency distributions and cross-tabulations. Results: The results showed that the majority of respondents were male (60.0%) and 13 years old (61.7%). Gadget use was dominated by the moderate category (60.0%), followed by the high category (23.3%) and the low category (16.7%). Cross-tabulations show that both male and female students are mostly in the moderate gadget use category, with the highest prevalence occurring at age 13. Conclusion: Gadget use among eighth-grade students was mostly in the moderate category. Suggestion: Based on these research findings, it is recommended that schools and parents supervise and educate students so that gadget use can be more judicious and balanced.